2012
DOI: 10.1111/j.1654-109x.2012.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation responses to long‐term alkaline cement dust pollution in Pinus sylvestris‐dominated boreal forests – niche breadth along the soil pH gradient

Abstract: Questions: How resilient is boreal forest vegetation growing on acidic podzols to the environmental change caused by alkaline kiln dust pollution? How adaptive is the vegetation, when species pool and time for dispersal do not limit? How constant is the species niche breadth along the soil pH gradient?Location: Region of 30 km around the Kunda cement plant, northern Estonia (59°30′ N, 26°32′ E), which has been continuously polluted last 140 years. Methods:We sampled 20 forest stands on sandy gleyic podzols at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Auerbach et al, 1997;Paal et al, 2010); at the same time several plant and lichen species can be found in the habitats where they normally do not grow (e.g. Marmor et al, 2010;Paal et al, 2013). Fine dust particles also pose a threat to human health, and can lead to respiratory and cardiovascular diseases (World Health Organization, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Auerbach et al, 1997;Paal et al, 2010); at the same time several plant and lichen species can be found in the habitats where they normally do not grow (e.g. Marmor et al, 2010;Paal et al, 2013). Fine dust particles also pose a threat to human health, and can lead to respiratory and cardiovascular diseases (World Health Organization, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…; Martin & Nilson ) and intense pollution near the plant caused the ‘nemoralization’ of the boreal forest community (Paal et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The study was performed in the region surrounding the town of Kunda (59°30 0 N, 26°32 0 E) in northern Estonia on the southern coast of the Gulf of Finland. The area within 50 km around the town hosts a diverse meta-pool of lichen species, as the region encompasses a high diversity of habitats from pine-dominated boreal and broadleaved nemoral forests (J€ uriado et al 2009;Paal et al 2013), and various soil types, fragments of sandstone and limestone escarpment (Raukas 1995).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Soil pH stands out as one of the most important edaphic predictors of plant species occurrence (Dupré and Ehrlén , Paal et al ). Although not a primary resource, it is regarded as a ‘master variable’ (Baar and Roelofs ) due to its control over the plant‐availability of nutrients and the presence of toxic cations (e.g.…”
mentioning
confidence: 99%